Effect of Varying Levels of Irrigation on the Yield and Water use of Cowpeas (Vigna Sinensis L.) - Singh, Surender; Lamba, P S; Sharma, H C (Annals of Arid Zone, 2016)
Effect of three soil moisture regimes viz. irrigation at IS, 35 and 5S per. cent available soil moisture, was studil1d on cowpeas variety Â·PS-6S’. Irrigating crop at higher soil moisture regimes increased the consumptive use values. The consumptive use values under It Iâ€¢â€¢ Is 5 and 105 regimes were 529.4, 567.2 and 626.S mm respectively. The maximum removal of soil moisture under all the soil moisture regimes was recorded from upper 0.20 cm depth which accounted for 51.17, 151.55 and 53.53 per cent of total consumptive use under It 5, Is 5 and 15 I) regimes respectively. A close relationship was recorded between actual consumptive use and Hargreaves equation at Hissar. As such this equation may be used for scheduling irrigation in summer cowpeas.